Coronary Intravascular Lithotripsy in a Tight Circumferential Calcified Lesion in the Presence of Haematoma Extending into Left Main Coronary Artery After Rotational Atherectomy - Jonathan Xinguo Fang; Arthur Sze-Yue Yung; Simon Cheung-Chi Lam; Frankie Chor-Cheung Tam (Interventional Cardiology: Reviews, Research, Resources)
Calcified disease increases procedural challenges and is associated with worse outcomes in percutaneous coronary intervention. Coronary intravascular lithotripsy is a new balloon-based modality for treating calcified disease with deep circumferential calcification. Its main benefit is simplicity and safety compared to atherectomy. However, atherectomy remains the modality of choice in balloon-uncrossable lesions. More than one modality is often needed for treatment of calcified disease. The authors present a case of a balloon-uncrossable calcified ostial left circumflex lesion which was first treated with rotational atherectomy. However, there was haematoma formation in the ostial circumflex extending into left main coronary artery, together with suboptimal preparation of calcified disease. Intravascular coronary lithotripsy was then used to successfully prepare the calcified lesion for stenting without causing extension of the haematoma.